2022
DOI: 10.1002/jpen.2458
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and development of cholestasis in surgical neonates receiving an intravenous mixed‐oil lipid emulsion

Abstract: Background Intestinal failure–associated liver disease (IFALD), initially manifesting as cholestasis, is a complication in neonates receiving parenteral nutrition (PN). Soybean oil lipid emulsion (SOLE), though implicated in IFALD, was the only US Food and Drug Administration (FDA)–approved initial intravenous lipid emulsion (ILE) for infants and children in the United States. A mixed‐oil lipid emulsion (MOLE) gained popularity in patients at risk for IFALD and was recently FDA approved as an initial ILE in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…However, only one randomized controlled trial showed that cholestasis was significantly lower in fish oil–containing ILEs (0% vs 18.2%; P = 0.011) in VLBW infants than in the pure soybean oil emulsion 23 . Recently, published retrospective studies showed that there was no significant difference in the incidence of PNAC in VLBW infants between SMOFlipid and Intralipid, 15,24–26 which is consistent with the conclusions drawn in this study. In the current study, which reported the incidence of cholestasis, no further comparisons were made between the two ILEs in VLBW infants.…”
Section: Discussionsupporting
confidence: 90%
“…However, only one randomized controlled trial showed that cholestasis was significantly lower in fish oil–containing ILEs (0% vs 18.2%; P = 0.011) in VLBW infants than in the pure soybean oil emulsion 23 . Recently, published retrospective studies showed that there was no significant difference in the incidence of PNAC in VLBW infants between SMOFlipid and Intralipid, 15,24–26 which is consistent with the conclusions drawn in this study. In the current study, which reported the incidence of cholestasis, no further comparisons were made between the two ILEs in VLBW infants.…”
Section: Discussionsupporting
confidence: 90%
“…One of the 7 studies, whose study population consisted of premature infants <34 weeks on 7 days of PN, found that those on composite ILE had significantly lower total bilirubin than those on soybean oil ILE (26). A more recent study by Yu et al (27) that examined neonates with gastrointestinal surgical conditions on ILE for 2 weeks found that infants on a lipid‐restricted soybean oil ILE (1 g/kg/day) had no differences in rates of cholestasis compared to a non‐lipid restricted mixed ILE (3 g/kg/day).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mix-oils lipid emulsion was characterized by a significantly shorter latency to developing cholestasis. The authors concluded that up to date, there is still no intravenous lipid emulsion able to prevent IFALD [ 28 ]. On the other hand, Daniel et al showed that in pediatric patients, administration of SMOFlipid was associated with a lower prevalence of IFALD than in patients receiving soybean oil-based lipid emulsion [ 29 ].…”
Section: Discussionmentioning
confidence: 99%